Drilling of bone: thermal osteonecrosis regions induced by drilling parameters - Mohd Faizal, Ali Akhbar; A. R., Yusoff (IOP Publishing, 2019)
In bone-drilling research, thermal osteonecrosis regions have onlybegun to be investigated. This study evaluates the thermal osteonecrosis regions and bone temperature elevations induced bydrilling parameters in drilling ofhuman cortical bone. The finite element method (FEM) was used to simulate the drilling simulation. The simulation results were then validated with the experimental bone- drilling test. Anewmethod called dimensionless weightage was proposed to evaluate the parameters that generate minimum thermal injury in bone-drilling. TheFEM results displayed the thermal injury in the bone as a function ofosteonecrosis diameter (OD), osteonecrosis depth (OH) andmaximum bone temperature elevation (Tmax). These results allow precise evaluation ofbone-drilling parameters’ influences on thermal damage. Results revealed that with the recommended parameter ranges, Tmax, OD, andOHcould be reduced up to 110.0 °C, 9.96 mmand 4.56 mm, respectively. This work represents a step toward the optimization ofbone-drilling parameters, which can provide an accurate approximation ofthermal damage in bone-drilling compared with previous research. Moreover, this work contributes valuable insights for engineers and clinicians to identify the favorable ranges